Antitumor effect of depsidones from lichens on tumor cell lines and experimental murine melanoma - Alexandrino,Caroline Almeida Farias (2019)
Abstract Lichens have exhibited numerous biological activities, including growth inhibition of tumor cells. This study evaluated the antiproliferative activity of hypostictic and salazinic acids against tumor cell lines (B16-F10, PC-03, MCF7, HT-29, HEP-G2, K562 and 786-0) by the SRB assay in vitro and antitumor activity in experimental murine melanoma in vivo. Activation of caspase-3 was quantified by flow cytometry. The murine experimental melanoma model B16-F10 was used in BALB/c mice for evaluation of antitumor activity. Hypostictic acid showed significant antiproliferative activity in K562 cells (GI50 2.20 µM), B16-F10 (GI50 13.78 µM) and 786-0 (GI50 14.24 µM), whereas salazinic acid was more active against K562 cells (GI50 64.36 µM), HT-29 (GI50 67.91 µM) and B16-F10 (GI5078.64 µM). Quantification of capase-3 revealed that the test compounds did not increase the expression of that enzyme. In the in vivo antitumor evaluation in B16-F10 melanoma, the isolated compounds inhibited tumor growth in relation to weight and volume. Hypostictic acid (16.7 mg/kg) inhibited 72% and salazinic acid 88% of tumor volume (p < 0.05). The results indicated that, both in the in vitro and in vivo models, the compounds evaluated showed antiproliferative and antitumor activities.